ANALISIS SOSIOLOGI SASTRA TERHADAP NOVEL LASKAR PELANGI Karya Andrea Hirata - Gani, Yuliana (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Objectives to be achhievd in this study areL1) how the relationship between the author and this work in the novel â€œLaskar Pelangiâ€.(2) describe aspects of the sociology of literature in the novel Laskar Pelangi the terms of character and characterization, social status, the behavior of the characters, as well as the events that occurred. This study is a review of sociology of literature using qualitative method. This research techniques include engineering data colletion, data conclusion, source of research data as the main data is the novel â€œLaskar Pelangiâ€ and several books related to literature and other sources. The results of these studies show that the aspect of sociology in the novel Laskar Pelangi is a reality that occurs in the Malay society oppressed Belitong proverty but they remain determinend to pursue the dream. This novel also tells the story of how friendship can be interwoven between the characters in the novel. Â  Keywords: sociology of literature, aqualitative, novel Laskar Pelangi